GAMBARAN PERILAKU GIZI PEKERJA GAMBANG YANG MENGALAMI OBESITAS DI KEBUN TEMBAKAU KLAMBIR V PTPN II MEDAN TAHUN 2012 - Yuni Hidayatun Siregar; Ernawati Nasution; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Obesity is a condition of excess body weight due to buried fat, due to the input  calories. In addition, the nutritional behavior also contribute to an increase in body weight. Obesity can impact on workers reduced worker productivity and can also lead to degenerative diseases. This study aims to determine the nutritional behavior of obese in tobacco plantation PTPN II Kelambir V Medan 2012. Type of this research is descriptive research designs, to get an overview of food consumption patterns, physical activity and nutritional status of workers experiencing obesity in gambang (sorting tobacco) tobacco  plantation kelambir V PTPN-II. The population of the research was that obese workers gambang (sorting tobacco) as many as 25 people. The samples were taken as many as 25 people with total sampling. Data collection is done with the interview using the food recall 24-hour, food frequency form and measurement of body weight and body height. The results showed that the nutritional behavior of workers based on the frequency of eating. The vegetables are sweet leaves, the type of drink is sweet tea, and for this type of fruit is a banana fruit consumed ≤ 3 x a week. The adequacy of the level of energy in the high category 64,00 % and total consumption proteins included in the category of very high 84,00%. Workers should the obese to gambang (sorting tobacco) pay more attention to the nutritional behavior, as well as the expected extension of a nutritional officer or from the clinic. Keywords : behavior nutrition, obesity, workers gambang (sorting tobacco)